KEBERSAMAAN DALAM RENTANGAN SEJARAH: KARAKTER KEGIATAN PENDIDIKAN - Rachmat Panca Putera (Insititut Agama Islam Agus Salim Metro Lampung, 2021)
This paper explains that in terms of process, education is a mature effort that marks the success or generation of its success include a change of behavior. But in terms of sociology, education is the effort of a generation and pass on cultural traditions and ways to develop the successor generation. In this regard it isessentially the same education history with the history of cultural inheritance between generations. This applies to various levels humans, whether individuals, groups, communities, tribes, or nations. Tradition and culture in generalrely on view live together. In Indonesia with a view of life so it is Pancasila. Proportionally when the history of education in Indonesia since independence, and instead of before, until now, various factors and educational activities are always associated with religious values. Because the first foundation of the nation and state in the Pancasila is prefixed with the Belief in God Almighty